2015
DOI: 10.4103/1319-2442.168596
|View full text |Cite
|
Sign up to set email alerts
|

Lactate dehydrogenase as a biomarker for early renal damage in patients with sickle cell disease

Abstract: Among many complications of sickle cell disease, renal failure is the main contributor to early mortality. It is present in up to 21% of patients with sickle cell disease. Although screening for microalbuminuria and proteinuria is the current acceptable practice to detect and follow renal damage in patients with sickle cell disease, there is a crucial need for other, more sensitive biomarkers. This becomes especially true knowing that those biomarkers start to appear only after more than 60% of the kidney func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Similarly to the studies with polymyxin B, KIM-1 concentration in the cell culture media or effluent was not indicative of the toxicity as the levels of KIM-1 decreased as cell death increased over time. LDH concentration, on the other hand, was significantly increased relative to controls in many of the treatments prior to falling off along with cell viability, indicating that it may be a more suitable biomarker for in vitro nephrotoxicity studies 59 .…”
Section: Discussionmentioning
confidence: 97%
“…Similarly to the studies with polymyxin B, KIM-1 concentration in the cell culture media or effluent was not indicative of the toxicity as the levels of KIM-1 decreased as cell death increased over time. LDH concentration, on the other hand, was significantly increased relative to controls in many of the treatments prior to falling off along with cell viability, indicating that it may be a more suitable biomarker for in vitro nephrotoxicity studies 59 .…”
Section: Discussionmentioning
confidence: 97%
“…Our study showed that LDH levels on the day 7 were associated with late mortality in AKI. Alzahri et al (2015) and Zager et al (2013) have demonstrated the relationship between LDH and kidney damage. Our study found that LDH can also be used in the prediction of mortality in patients with AKI.…”
Section: Discussionmentioning
confidence: 99%
“…The positive association between albuminuria and LDH suggest the central role of hemolysis as the starting point for many of the subsequent complications of SCA, including kidney damage [14, 18]. A Previous study has already reported a significant correlation between serum LDH levels and albuminuria [19]. Indeed, hemolysis through increased plasma-free hemoglobin concentrations can induce the generation of ROS by non-enzymatic (Fenton reaction) with subsequent oxidative stress, inflammation, endothelial dysfunction and tissue damage [14, 19].…”
Section: Discussionmentioning
confidence: 99%
“…A Previous study has already reported a significant correlation between serum LDH levels and albuminuria [19]. Indeed, hemolysis through increased plasma-free hemoglobin concentrations can induce the generation of ROS by non-enzymatic (Fenton reaction) with subsequent oxidative stress, inflammation, endothelial dysfunction and tissue damage [14, 19]. However, the hemolytic origin of circulating LDH remains a matter of controversy.…”
Section: Discussionmentioning
confidence: 99%